Vertical shear resistance of noncompact steel–concrete composite girders under combined positive moment and shear - Pengfei Men; Bowen Liang; Wuchao He; Jin Di; Fengjiang Qin; Zhigang Zhang (Case Studies in Construction Materials, 2023)
For noncompact composite girders widely employed in bridge structures, the design can be more reasonable and economical if the shear contribution of concrete slabs is considered. In this study, the ultimate shear resistance of composite girders with noncompact sections under positive moments was investigated using the finite element method (FEM). The validity of the FEM was verified using existing test data. Subsequently, parametric studies were performed using the validated FEM. It was shown that the concrete slab thickness and web height-to-thickness ratio had notable effects on the shear resistance of the slab; the concrete slab width had a negligible effect on the shear resistance if its value exceeded twice the web height; the web aspect ratio mainly affected the shear resistance of the web. The numerical results indicated that the shear resistance of the composite girder was 1.02–1.63 times of that calculated using the ASSHTO code, and 1.12–1.55 times of that calculated using the EC4 code. After comprehensively considering the effects of these parameters, a design equation for predicting the shear resistance of noncompact composite girders under positive moments was suggested and verified using numerical and test data.